Select the best. Positive selection to improve farm saved seed potatoes. Trainers manual. - Gildemacher, P.; Demo, P.; Kinyae, P.; Wakahiu, M.; Nyongesa, M.; Zschocke, T. (International Potato Center, 2007)
This training manual is designed to provide step-by step instructions to trainers in teaching potato farmers positive selection, that is, to ‘select the best’. Positive selection can be used to improve the quality of the seed potatoes saved from the farmers own crop. The manual contains two major sections. The first section provides the background behind the technology: what are the major seed borne potato diseases; when can ‘select the best’ be helpful; and how does it actually work. The second section outlines the training program to teach positive selection to a farmer group. The heart of the training program is a demonstration experiment. The training methodology is based on learning by doing, using the field as the classroom.